Epidemiology of rumen fluke infection in selected buffalo farms in perak, malaysia: prevalence, molecular species identification, and associated risk factors - Ahmad Tookhy, Nazir; Md Isa, Nur-Mahiza; Abd Rahaman, Yasmin; Ahmad, Nur Indah; Sharma, Reuben Sunil Kumar; Idris, Lokman Hakim; Mansor, Rozaihan; Bui, Dung Thi; Hamzah, Noor Hazfalinda; Shakhes, Shoaib Ahmad (Springer Science and Business Media Deutschland, 2024)
Rumen flukes cause heavy economic losses in the ruminant industry worldwide, especially in tropical and subtropical countries. This study estimated the prevalence of rumen flukes in buffaloes, identified the species diversity, and determined risk factors associated with rumen fluke prevalence in Perak, Peninsular Malaysia. A cross-sectional study was conducted, and 321 faecal samples were collected from six buffalo farms. A structured questionnaire was developed, and farmers were interviewed to obtain information regarding risk factors associated with rumen fluke infection. The faecal samples were examined using sedimentation and Flukefinder® techniques. Genomic DNA was extracted from the fluke eggs recovered using the Flukefinder® method, and the internal transcribed spacer 2 (ITS2) fragment was amplified and sequenced to facilitate species identification. The results showed that the overall prevalence of rumen fluke across the sampled farms was 40.2% (129/321). Three rumen fluke species were identified, namely, Fischoederius elongatus, F. cobboldi, and Orthocoelium streptocoelium. Several management factors had a significant association (P < 0.05) with rumen fluke prevalence, including production type, cleaning of the stable, drinking water system, flooding around the farm, grazing system, pasture sharing with other livestock, and deworming program. This work constitutes the first attempt to understand the epidemiology of rumen fluke infection in the region and suggests that good farm management, pasture management, choosing appropriate drugs, and proper husbandry practices may improve buffalo health and production in areas where rumen flukes are prevalent.